ANALISIS KELAYAKAN ISI BUKU TEKS BAHASA INDONESIA TERBITAN ERLANGGA KELAS IX SMP/ MTS SEMESTER I - Ananda Sofia Syahla Nanda (STKIP Subang, 2022)
Textbooks are one of the academic needs of schools that cannot be separated from the existence of classes. The use of textbooks is based on the current curriculum so that there are no errors in understanding the content of the material. This study aims to analyze the feasibility of Indonesian language textbooks for class IX odd semester in Erlangga Books. The research method used is descriptive qualitative research. By using data collection techniques, namely the study of text documents and interviews. There are two sources of data used in this study, namely primary data and secondary data. The primary data used in this study were interviews with a teacher who teaches Indonesian subjects and six students at MTS Sirnamiskin. The secondary data used in this research is to use documents or Indonesian language textbooks with the title